In vitro antibacterial effects of statins against bacterial pathogens causing skin infections - Ko, H.; Lareu, R.; Dix, B.; Hughes, Jeff (Springer, 2018)
© 2018 Springer-Verlag GmbH Germany, part of Springer Nature With financial considerations impeding research and development of new antibiotics, drug repurposing (finding new indications for old drugs) emerges as a feasible alternative. Statins are extensively prescribed around the world to lower cholesterol, but they also possess inherent antimicrobial properties. This study identifies statins with the greatest potential to be repurposed as topical antibiotics and postulates a mechanism of action for statins’ antibacterial activity. Using broth microdilution, the direct antibacterial effects of all seven parent statins currently registered for human use and three selected statin metabolites were tested against bacterial skin pathogens Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Serratia marcescens. Simvastatin and pitavastatin lactone exerted the greatest antibacterial effects (minimum inhibitory concentrations of 64 and 128 µg/mL, respectively) against S. aureus. None of the statins tested were effective against E. coli, P. aeruginosa, or S. marcescens, but simvastatin hydroxy acid acid might be active against S. aureus, E. coli, and S. marcescens at drug concentrations > 256 µg/mL. It was found that S. aureus may exhibit a paradoxical growth effect when exposed to simvastatin; thus, treatment failure at high drug concentrations is theoretically probable. Through structure-activity relationship analysis, we postulate that statins’ antibacterial action may involve disrupting the teichoic acid structures or decreasing the number of alanine residues present on Gram-positive bacterial cell surfaces, which could reduce biofilm formation, diminish bacterial adhesion to environmental surfaces, or impede S. aureus cell division.